Chemokine C‐C motif ligand 21 synergized with programmed death‐ligand 1 blockade restrains tumor growth. Issue 11 (7th September 2021) - Chen, Qiangda; Yin, Hanlin; Pu, Ning; Zhang, Jicheng; Zhao, Guochao; Lou, Wenhui; Wu, Wenchuan
Abstract: Programmed death‐ligand 1 (PD‐L1) blockade has revolutionized the prognosis of several cancers, but shows a weak effect on pancreatic cancer (PC) due to poor effective immune infiltration. Chemokine C‐C motif ligand 21 (CCL21), a chemokine promoting T cell immunity by recruiting and colocalizing dendritic cells (DCs) and T cells, serves as a potential antitumor agent in many cancers. However, its antitumor response and mechanism combined with PD‐L1 blockade in PC remain unclear. In our study, we found CCL21 played an important role in leukocyte chemotaxis, inflammatory response, and positive regulation of PI3K‐AKT signaling in PC using Metascape and gene set enrichment analysis. The CCL21 level was verified to be positively correlated with infiltration of CD8 + T cells by the CIBERSORT algorithm, but no significant difference in survival was observed in either The Cancer Genome Atlas or the International Cancer Genome Consortium cohort when stratified by CCL21 expression. Additionally, we found the growth rate of allograft tumors was reduced and T cell infiltration was increased, but tumor PD‐L1 abundance elevated simultaneously in the CCL21‐overexpressed tumors. Then, CCL21 was further verified to increase tumor PD‐L1 level through the AKT‐glycogen synthase kinase‐3β axis in human PC cells, which partly impaired the antitumor T cell immunity. Finally, the combination of CCL21 and PD‐L1 blockade showed superior synergistic tumor suppression in vitro and in vivo. Together, our findings suggested that CCL21 in combination with PD‐L1 blockade might be an efficient and promising option for the treatment of PC. Abstract : Chemokine C‐C motif ligand 21 (CCL21) in the tumor microenvironment can promote T cell infiltration and enhance their antitumor immune response. However, CCL21 also stabilizes and upregulates programmed death‐ligand 1 (PD‐L1) expression on pancreatic cancer cells through the AKT‐glycogen synthase kinase‐3β signaling pathway at the same time, which could partly impair the local immune response. Thus, PD‐L1 blockade was used in combination with CCL21, which showed a powerful synergism and promising therapeutic efficacy.